Rice Seedling Growth Promotion by Biochar Varies With Genotypes and Application Dosages - Liu, Minglong; Lin, Zhi; Ke, Xianlin; Fan, Xiaorong; Joseph, Stephen; Taherymoosavi, Sarasadat; Liu, Xiaoyu; Bian, Rongjun; Solaiman, Zakaria M.; Li, Lianqing; Pan, Genxing (Frontiers in Plant Science, 2021)
While biochar use in agriculture was widely advocated, how biochar’s effect on plant growth varied with biochar forms and crop genotypes was poorly addressed. The role of dissolvable organic matter (DOM) in plant growth had been increasingly addressed for crop production with biochar. In this study, a hydroponic culture of rice seedling growth of two cultivars was treated with bulk mass (DOM contained), water-extract (DOM only) and the extracted residue (DOM-free) of maize residue biochar, at a volumetric dosage respectively of 0.01%, 0.05% and 0.10%. On seedling root growth of the two cultivars, bulk biochar exerted a generally negative effect while biochar extract had a consistently positive effect across application dosages. Differently, extracted biochar showed a contrasting effect between genotypes. In another hydroponic culture with Wuyunjing 7 cultivar treated with biochar extract at sequential dosages, seedling growth was promoted by 95% at 0.01% dosage but by 26% at 0.1% dosage, explained with great promotion of secondary roots rather than of primary roots. Such effects were likely explained with the low molecular weight organic acids and nanoparticles contained in biochar DOM. This study highlights the importance of biochar DOM and crop genotype when evaluating the biochar’s effect on plant. And use of low dosage of biochar DOM could help farmers to adopt biochar technology as a solution to agricultural sustainability.